2006
DOI: 10.1073/pnas.0510322103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved bacterial protein secretion system in Vibrio cholerae using the Dictyostelium host model system

Abstract: The bacterium Vibrio cholerae, like other human pathogens that reside in environmental reservoirs, survives predation by unicellular eukaryotes. Strains of the O1 and O139 serogroups cause cholera, whereas non-O1͞non-O139 strains cause human infections through poorly defined mechanisms. Using Dictyostelium discoideum as a model host, we have identified a virulence mechanism in a non-O1͞non-O139 V. cholerae strain that involves extracellular translocation of proteins that lack N-terminal hydrophobic leader sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
1,349
4
24

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,030 publications
(1,402 citation statements)
references
References 37 publications
25
1,349
4
24
Order By: Relevance
“…We generated mutants of both sciG (the clpV ortholog), and sciS (the icmF ortholog), genes which have been established as essential for T6SS assembly and functional secretion in other systems (6,42). When mice were infected with wild-type and mutant strains of S. Typhimurium, mice infected with the mutant strains reached an endpoint approximately 1 to 2 days later than mice infected with wild-type S. Typhimurium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We generated mutants of both sciG (the clpV ortholog), and sciS (the icmF ortholog), genes which have been established as essential for T6SS assembly and functional secretion in other systems (6,42). When mice were infected with wild-type and mutant strains of S. Typhimurium, mice infected with the mutant strains reached an endpoint approximately 1 to 2 days later than mice infected with wild-type S. Typhimurium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many Gram-negative bacteria encode a molecular machine called the T6SS that is dedicated to target and kill other bacteria and sometimes to inject effector proteins into eukaryotic cells (10). For example, the human pathogen V. cholerae employs the T6SS to kill E. coli or to disable the amoebae Dictyostelium discoideum and macrophage cell lines (14,48,49). Recent studies demonstrated that T6SS organelles in V. cholerae, P. aeruginosa, and entero-aggregative E. coli cells are very dynamic and likely expel their T6SS spike/tube VgrG/Hcp complex toward prokaryotic cells and cause target cell lysis by delivering antibacterial toxins (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…In other bacteria, type VI secretion systems are responsible for secretion of molecules that are capable of disabling the host immune response. For example, proteins secreted via the type VI secretion system described in Vibrio cholera are responsible for cytotoxicity in mammalian macrophages (38). Porphyromonas gingivalis utilizes type VI secretion to expel gingipain proteases.…”
Section: Discussionmentioning
confidence: 99%